A new stratified risk assessment tool for whiplash injuries developed from a prospective observational study. Issue 1 (30th January 2013) - Kasch, Helge; Kongsted, Alice; Qerama, Erisela; Bach, Flemming W; Bendix, Tom; Jensen, Troels Staehelin
Abstract : Objectives: An initial stratification of acute whiplash patients into seven risk-strata in relation to 1-year work disability as primary outcome is presented. Design: The design was an observational prospective study of risk factors embedded in a randomised controlled study. Setting: Acute whiplash patients from units, general practitioners in four Danish counties were referred to two research centres. Participants: During a 2-year inclusion period, acute consecutive whiplash-injured (age 18–70 years, rear-end or frontal-end car accident and WAD (whiplash-associated disorders) grades I–III, symptoms within 72 h, examination prior to 10 days postinjury, capable of written/spoken Danish, without other injuries/fractures, pre-existing significant somatic/psychiatric disorder, drug/alcohol abuse and previous significant pain/headache). 688 (438 women and 250 men) participants were interviewed and examined by a study nurse after 5 days; 605 were completed after 1 year. A risk score which included items of initial neck pain/headache intensity, a number of non-painful complaints and active neck mobility was applied. The primary outcome parameter was 1-year work disability. Results: The risk score and number of sick-listing days were related (Kruskal-Wallis, p<0.0001). In stratum 1, less than 4%, but in stratum 7, 68% were work-disabled after 1 year. Early work assessment (p<0.0001), impact of the event questionnaire (p<0.0006), psychophysical pain measures being McGill pain questionnaire parameters (p<0.0001), pressure pain algometry (p<0.0001) and palpation (p<0.0001) showed a significant relationship with risk stratification. Analysis: Findings confirm previous studies reporting intense neck pain/headache and distress as predictors for work disability after whiplash. Neck-mobility was a strong predictor in this study; however, it was a more inconsistent predictor in other studies. Conclusions: Application of the risk assessment score and use of the risk strata system may be beneficial in future studies and may be considered as a valuable tool to assess return-to-work following injuries; however, further studies are needed.